Expanded distribution and predicted suitable habitat for the critically endangered yellow‐tailed woolly monkey (Lagothrix flavicauda) in Perú. Issue 2 (15th January 2023) - Zarate, Melissa A.; Shanee, Sam; Charpentier, Elvis; Sarmiento, Yeissy; Schmitt, Christopher A.
Abstract: The Tropical Andes Biodiversity Hotspot holds a remarkable number of species at risk of extinction due to anthropogenic habitat loss, hunting, and climate change. One of these species, the critically endangered yellow‐tailed woolly monkey ( Lagothrix flavicauda ), was recently observed in the region Junín, 206 km south of its previously known distribution. This range extension, combined with continued habitat loss, calls for a reevaluation of the species distribution, and available suitable habitat. Here, we present novel data from surveys at 53 sites in the regions of Junín, Cerro de Pasco, Ayacucho, and Cusco. We encountered L. flavicauda at 9 sites, all in Junín, and the congeneric Lagothrix lagotricha tschudii at 20 sites, but never in sympatry. Using these new localities along with all previous geographic localities for the species, we made predictive species distribution models based on ecological niche modeling using a generalized linear model and maximum entropy. Each model incorporated bioclimatic variables, forest cover, vegetation measurements, and elevation as predictor variables. The model evaluation showed >80% accuracy for all measures. Precipitation was the strongest predictor of species presence. Habitat suitability maps illustrate potential corridors for gene flow between the southern and northern populations, although much of this area is inhabited by L. l. tschudii whereas L. flavicauda has yet to be officially confirmed in these areas, by these or any other scientific surveys. An analysis of the current protected area (PA) network showed that 75% of remaining suitable habitat is unprotected. With this, we suggest priority areas for new PAs or expansions to existing reserves that would conserve potential corridors between L. flavicauda populations. Further surveys and characterization of the distribution in intermediate areas, combined with studies on gene flow through these areas, are still needed to protect this species. Abstract : Summary of our project workflow—from novel surveys for yellow‐tailed woolly monkeys in central Perú to habitat suitability modeling to overlaying current protected areas (PA) on suitable habitat. We find that current PA are inadequate for conservation. Research highlights: Our survey results showed observations of the yellow‐tailed woolly monkey ( Lagothrix flavicauda ) only in central Junín near where a seemingly‐isolated population was found far outside of the originally documented geographic range in 2018. Both types of species distribution models used—the generalized linear model and the maximum entropy model—showed that the species presence was most strongly (and negatively) correlated with the environmental variable of precipitation seasonality. Predicted suitable habitat is shown throughout Junín and Pasco. Overlaying the Peruvian protected area network over this area revealed that 75% of suitable yellow‐tailed woolly monkey habitat is unprotected.